Comercialização de hortifrutigranjeiros em Itabaiana-SE - Carvalho, Diana Mendonça de (2010)
The present study of agricultural marketing in Itabaiana city analyzed the structure, form, function and process, from the identification and demonstration of the main horticultural imports and exports for this market. In this sense, the research aimed to reflect the dynamic socio-spatial and economic for the marketing of fresh produce in the city. This was justified in desire to contribute to the knowledge of trade and to check the flows and networks established in this space. Therefore, it assumed the direct and indirect observations of facts, through field work, with interviews of various social actors, including: farmers, traders, wholesalers, market traders and supermarkets, interviews and survey data federal, state and municipal and literature research. Information obtained testified that agricultural marketing is a complex activity among those involving the steps of the agriculture production, because it includes several segments that appropriate the production. This process is found in Brazil in the state of Sergipe and more specifically in Itabaiana city, the integration of various social actors in the production chain. In Itabaiana, the establishment of several chains of agricultural products was favored by natural conditions, the suitable farming practices, the historical events that made the city a crossing point between the coast and hinterland, the economic base in trade and agriculture; the "truck culture" that encouraged the import and export of these products. These chains and more specifically agricultural marketing in Itabaiana have been controlled by agents that promote the import and distribution of horticultural and thus feed the formal and informal markets, both local and regional scale. In this way, agricultural marketing has contributed to Itabaiana firm as the largest wholesale market in Sergipe, competing in terms of commercial appeal, with the major wholesaler markets in the Northeast.